Assessment of maternal and perinatal outcome in cases of prolonged pregnancy in a tertiary healthcare institute: a cross sectional observational study - Ghumare, Jitendra Pundlik; Bargaje, Ganesh Mahadeo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Prolonged pregnancy has always been regarded as a high‑risk condition because perinatal morbidity and mortality is known to rise. The interest in postdatism (just beyond expected date of delivery) has been recent and the management is controversial, more so with the advent of sonography providing information about placental aging and amount of amniotic fluid. The aim of the present retrospective study was to analyze the outcome of pregnancies which crossed the expected date of delivery. Methods: The present study was a cross sectional observational study, conducted between April 2018 to September 2018, among 90 cases presented with post dated pregnancy under the department of obstetrics and gynecology, in a tertiary medical teaching institute in Maharashtra. Results: Maximum number of cases, i.e., 22.22% indications were meconium stained liquor with fetal distress, in 18.51% cases indications were failure of induction, in 22.22% indications were nonreactive NST, in 17.61% cases indications were CPD. Conclusions: It was concluded that prolonged pregnancy was associated with significant risk of perinatal complications such as fetal distress, meconium aspiration syndrome and IUGR.